Design and Evaluation of Collaborative Learning Management System (CLMS) Framework for Teaching Technical Subject - Yusoff, Siti Rosni Mohamad; Mat Zin, Nor Azan (New Horizons in Web Based Learning, 2014)
This paper discuss the design and usability testing of a proposed Collaborative Learning Management System (CLMS) framework for technical subject teaching. The design and development of the system are based on ADDIE model. The web based learning platform was assembled using an Open Source Learning Management System (LMS). Sixty five student teachers in Bachelor of Teaching and Design Technology programme participated in the study. The results show that the system is usable to assist collaborative learning activities for teaching technical subject, support classroom learning, support communication with peers and instructors, increases motivation to discuss course work, coordinates learning materials and able to recall prior knowledge. Technical (Distributed Denial of Service attack (DDoS attack)), low graphic editing skill and netiqutte issues were encountered during the usability testing.